2011
DOI: 10.1111/j.1749-124x.2011.01238.x
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Specialization and Trade Growth in Northeast Asia

Abstract: As the global economy has become further integrated, the international production chain has become more sophisticated, with diversified stages of production located in different countries. Economic theorists have argued that the fragmentation of the global production chain is partly attributable to the high growth in international trade over the past several decades. In this study, we examine vertical specialization in China, Japan and Korea, and its contribution to these nations' trade. Using a multilevel mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…2 The literature (e.g. Ping, 2005;Hwang et al, 2011) documents that prior to 2005, China's VS share rose sharply. Ping (2005) showed that it soared from 14% in 1992 to 22% in 2002, an increase that had previously taken most OECD countries about 20 years to achieve.…”
Section: Introductionmentioning
confidence: 99%
“…2 The literature (e.g. Ping, 2005;Hwang et al, 2011) documents that prior to 2005, China's VS share rose sharply. Ping (2005) showed that it soared from 14% in 1992 to 22% in 2002, an increase that had previously taken most OECD countries about 20 years to achieve.…”
Section: Introductionmentioning
confidence: 99%